Opening of IMI's new headquarters - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The opening of the magnificent new centre of CAB International's International Mycological Institute (IMI) was performed by Dr M S Swaminathan, World Food Prize Laureate, on 14 June 1993. The Institute was relocated from Kew to Bakeham Lane. Egham,...